Memaknai Communio dalam Umat Kristen Berdasarkan Efesus 4:5 - Jindung, Pilipus Benizi; Firman, Karifansius; Sandri, Yohanes Arnoldus (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
The development of information and communication technology (ICT) has had a significant impact on religious life, including the fellowship of Christians. ICT offers opportunities to expand the reach of ministry, strengthen connections between congregations, and facilitate Bible learning. However, potential dangers also exist; ICT can erode the values of communion and fuel individualism, contrary to the teachings of Christ. Ephesians 4:5 ("One Lord, one faith, one baptism") provides an analytical framework for understanding this impact. Oneness in God, faith, and baptism should be a solid foundation of fellowship, transcending differences. However, social media and the internet create a fragmented "virtual world", isolating individuals in a limited information "bubble". Online interaction, while beneficial, does not completely replace the face-to-face meetings that are essential for building real relationships. Social media algorithms amplify "filter bubbles," creating polarization and inhibiting constructive dialogue. Self-comparisons on social media can also trigger jealousy and division. To address this, churches need to make wise use of ICT, build positive and inclusive online communities, and emphasize the importance of face-to-face meetings and real ministry. Education on the healthy use of ICT is also crucial, so that communion is maintained and Christian values remain firmly entrenched.